Golden Cane Furniture Manufacturing Company a production systems study - Crisostomo, Catherine Q. (College of Engineering, 1992)
Last year, the Department of Sceicne and Technology (DOST) through the Technology Application and Promotion Institute (TAPI) put up a program with the objective of improving the technology and increasing efficiency of the country's export industries. In connection with this, the UP College of Engineering Department of Industrial Engineering and Operations Reserch was tapped to make a productivity study on a medium-scale industry, the Golden Cane Furniture Mfg. Corp (GC) the result was overwhelming; the GC management has been very receptive and enthusiastic regarding the implementation of the recommendations put forth by the study. Considerable changes have already been made right after the study was presented. Some of which are easily implementable and the others, conceived as implementable within the next few months. One of these recommendations is the undertaking of a Production Systems Study on the company that would tackle all the details prescribed in the Productivity Study. It was on this footing where this study was put forth. A study team composed of three fourth year Industrial Engineering undergraduates presently taking up a course in Systems of Production (IE 151) was formed. Gathering, processing, and analysis of data was one through actual observation, interviews, and secondary sources. The Total Systems Approach was used in the analysis and generation of solutions for the system under study. Upon the analysis of the company's Production System, four main areas surfaced as the core problems from which other problems arise: a. Unclearly defined organizational functions and responsibilities; b. weak management information system; c. proper worker orientation and attitude; and d. lack of proper techniques in Production Planning, and Control.Based on this findings , the study generated alternatives and came out with the following recommendations: a. a definition of the organizational functions and responsibilities; b. improvement of management information system; c. implementation of standard forms and procedures; d. formulation of Quality Circles and Company Quality Policies; e. training and retraining of newly hired and old workers and supervisors; and f. adoption of Production / Operations Management techniques, i.e. Forecasting, Capacity Planning. prescribed solutions for further consideration were as follows: a. improvement of existing facilities (e.g. comfort facilities); b. observation of "good housekeeping", and c. installation of additional exhaust fans, fire-fighting equipment, first-aid cabinets, drinking fountains, and lockers. After one-and-a-half months, the study team presented its progress report to the class and to the study adviser for initial deliberation. Necessary additions and improvements were made based on the results of the presentation. After two weeks, the study team then presented to the GC Management the major findings and recommendations of the study, where the officers expressed support and enthusiasm on the generated solutions to the existing problems.